Loosing Your Best Talent: Can Leadership Retain Employees? The Dilemma of the Banking Sector of Hyderabad Sindh, Pakistan: A Mediation Investigation - Nadeem Khalid; Munwar Hussain Pahi; Umair Ahmed (International Review of Management and Marketing, 2016)
Country expects that commercial banking systems contribute to the overall development, but this development depends upon qualified and competent employees of the commercial banks institutions. Retaining this resource is of utmost importance for higher commercial banks. However, commercial banks are finding it hard to retain competent and qualified faculty in the face of competition from the industry. Retention is becoming a big dilemma for developing countries. The present study investigates the relationship between leadership style, job satisfaction, organization commitment and retention of employee in commercial banks of Sindh, Pakistan. The data was collected from the commercial bank of Sindh whereby, SmartPLS 2.0 was used for data analysis. The results have indicated a strong and positive relationship between leadership style and employee retention. Job satisfaction and organization commitment mediate the relationship between leadership style and employees retention. This study is significant for top management of commercial banks who are facing retention problems. Findings of study could provide them with guidelines regarding to how the leadership style retain talent employees in the commercial bank. Limitation and Future reconditions also discussed.